Analisis Tingkat Risiko Bahaya pada Proses Pengiriman Bahan Bakar Minyak (BBM) Menggunakan Metode Hazard Identification Risk Assessment (HIRA) - Sindy Anggraeni; Agustian Suseno (Jurnal Migasian, 2022)
In preventing work accidents in every work activity, it is necessary to look at the potential hazards and risks that may be caused by the work. In this study, the hazard identification risk assessment method was applied to identify potential hazards that might occur in the process of sending fuel oil and evaluating it byassessing the risks of potential hazards that arise based on the risk matrix in the process of sending fuel oil at PT. XYZ. The two variables studied are likelihood and severity. The techniques used in data collection are observation and interviews. Observations were made by observing the work area to obtain the actual data needed in the research and interviews were conducted with the company's safety officers. After identification there are 24 potential hazards that can cause work accidents. The highest risk level value is 46% in the high risk category and the extreme risk level value is in the fuel delivery process with hazard sources in road conditions. Hazard control refers to the hierarchy of occupational safety and health, namely elimination, administrative controls and personal protective equipment.